Project management accounting budgeting, tracking, and reporting costs and profitability - Callahan, Kevin R.; Stetz, Gary S. 1962-; Brooks, Lynne M. (John Wiley & Sons, Inc., 2011)
"Helping project managers figure out how costs interact with the general ledger as well as make decisions about whether to continue with the project as planned, this book reveals how project expensing should be capitalized or expensed in order to keep the budget on track and improve profitability. This book helps business professionals determine the greatest tax/cost savings by through understanding what portion of the project can be capitalized. Along with new case studies, new material has been added on risk assessment of managing projects"--Provided by publisher.